Angiotensin receptor blockers and β-blockers in Marfan syndrome: an individual-patient-data meta-analysis of randomised trials - Pitcher, A; Spata, E; Emberson, J; Baigent, C; Reith, C (Elsevier, 2022)
Background: Angiotensin receptor blockers (ARBs) and β blockers are widely used in the treatment of Marfan syndrome to try to reduce the rate of progressive aortic root enlargement characteristic of this condition, but their separate and joint effects are uncertain. We aimed to determine these effects in a collaborative individual patient data meta-analysis of randomised trials of these treatments.